Implementation of Singing Method to Improve Early Childhood Language Skills at RA Tarbiyatul Aulad - Khasanah, Uswatun; Puryanti, Wahyu (ETNOPEDAGOGI: Jurnal Pendidikan dan Kebudayaan, 2024)
This study aims to describe the application of the singing method in improving the language skills of early childhood at RA Tarbiyatul Aulad. Language skills are an important aspect in the development of early childhood that plays a role in communication and social interaction. The singing method is used as one of the interesting and enjoyable learning strategies for children. This study uses a descriptive qualitative approach with data collection techniques in the form of observation, interviews, and documentation. The subjects of the study were children in group A at RA Tarbiyatul Aulad. The results of the study showed that the singing method was able to improve children's language skills, both in terms of vocabulary, pronunciation, and courage to speak in front of their friends. The songs used in learning are adjusted to the theme and level of child development so that it is easier for children to understand the contents of the song and enrich new vocabulary. In addition, the singing method is also able to create a pleasant learning atmosphere, increase self-confidence, and train children's concentration. The application of this method routinely and in a structured manner has proven effective in supporting the language development of early childhood. This study recommends the use of the singing method as an alternative to innovative and enjoyable language learning in early childhood education institutions